Influence of weight and size of corn seeds on field performance - Silva, Walter Rodrigues da; Marcos Filho, Julio (Pesquisa Agropecuaria Brasileira, 2014)
This study, conducted at Piracicaba, SP, Brazil, during 1976/77, was to evaluate the effects of weight and size of corn (Zea mays L.) seeds upon field performance. Seeds of the double hybrid AG-152R and of the Piranão variety were pre-cleaned, separated by weight in a gravity separator (heavy and light fractions) and upgraded in two size classes, by using 20/64 and 24/64 inches screens. Samples were taken prior to separation by weight and size. The treatments for each variety thus obtained were caracterized as to moisture content, purity, thousand-seed weight, bulk weight and density. Field studies comprised tests of emergency, plant height, final stand and yield. The weight and size of seeds had no effect on field performance in the test conducted, for both cultivars. On the other hand, the gravity separator was considered to be an efficient equipment for the separation of unit and volume weight, even when the seeds of different sire classes were used.
Keywords: Zea mays L; performance of seeds in laboratory; vigor tests